Experimental investigation on synthesis, characterization, stability, thermo-physical properties and rheological behavior of MWCNTs-kapok seed oil based nanofluid - Hameed, A. (2019)
Several researchers devoted their efforts for the thermal conductivity enhancement of Carbon Nanotubes (CNTs) based nanofluids as CNTs have excellent thermal properties. However, limited research is reported on the detailed thermo-physical properties of CNTs and oil based nanofluids. In this work, the one-step method synthesis of a new MWCNTs-Kapok seed oil based nanofluid at constant nanoparticle concentration (0.1 wt./wt.) is reported. The nanofluid is characterized by FESEM, FTIR, visual stability analysis and thermophysical properties are experimentally measured. The viscosity found in the range of (0.049â10.101 PaÂ·s), the thermal conductivity of (0.165â0.207 W/mÂ·K) and enhancement of thermal conductivity (6.1538) were observed. Moreover, the viscosity decreases, and thermal conductivity increases with an increase in temperature. The experimentally obtained data are found in agreement with existing models and modified correlations. The rheological behavior showed that nanofluid is non-Newtonian in nature and exhibiting shear thinning or pseudo plastic behavior. Â© 2018